Strengthening and strain hardening mechanisms in a precipitation-hardened high-Mn lightweight steel. (November 2017) - Yao, M.J.; Welsch, E.; Ponge, D.; Haghighat, S.M.H.; Sandlöbes, S.; Choi, P.; Herbig, M.; Bleskov, I.; Hickel, T.; Lipinska-Chwalek, M.; Shanthraj, P.; Scheu, C.; et al.
Abstract: We report on the strengthening and strain hardening mechanisms in an aged high-Mn lightweight steel (Fe-30.4Mn-8Al-1.2C, wt.%) studied by electron channeling contrast imaging (ECCI), transmission electron microscopy (TEM), atom probe tomography (APT) and correlative TEM/APT. Upon isothermal annealing at 600 °C, nano-sized κ-carbides form, as characterized by TEM and APT. The resultant alloy exhibits high strength and excellent ductility accompanied by a high constant strain hardening rate. In comparison to the as-quenched κ-free state, the precipitation of κ-carbides leads to a significant increase in yield strength (∼480 MPa) without sacrificing much tensile elongation. To study the strengthening and strain hardening behavior of the precipitation-hardened material, deformation microstructures were analyzed at different strain levels. TEM and correlative TEM/APT results show that the κ-carbides are primarily sheared by lattice dislocations, gliding on the typical face-centered-cubic (fcc) slip system {111}<110>, leading to particle dissolution and solute segregation. Ordering strengthening is the predominant strengthening mechanism. As the deformation substructure is characterized by planar slip bands, we quantitatively studied the evolution of the slip band spacing during straining to understand the strain hardening behavior. A good agreement between the calculated flow stresses and the experimental data suggests that dynamic slip band refinement is the main strain hardening mechanism. The influence of κ-carbides on mechanical properties is discussed by comparing the results with that of the same alloy in the as-quenched, κ-free state. Graphical abstract: Image